Manipulating interstitial carbon atoms in the nickel octahedral site for highly efficient hydrogenation of alkyne - Yiming Niu (Nature Portfolio, 2020)
Design and synthesis of non-noble metal catalysts is crucial for highly-efficient hydrogenation. Here, the interstitial sites in nickel are manipulated with zinc and filled by dissociated carbon atoms, which drastically improve the selectivity/stability in acetylene hydrogenation reaction.